Indonesian Islamic socialism and its South Asian roots - Fogg, K (Cambridge University Press, 2019)
Islamic socialism was a major intellectual and political movement in Indonesia in the twentieth century, with ongoing influences until today. However, this movement did not follow the most common narratives of Indonesian intellectual history, which trace religious influences to the Middle East and political movements to anti-colonial reaction in terms framed by the Dutch. Rather, the first major Indonesian proponent of Islamic socialism, H. O. S. Tjokroaminoto, took his thinking on Islamic socialism directly from the English-language work of a South Asian itinerant scholar, Mushir Hosein Kidwai, in a process that most likely had the minority Ahmadiyyah community as intermediaries. Future Islamic socialist thought, much of it influenced by Tjokroaminoto, continued to echo through Indonesian secular nationalism, political Islam, and even Islamism. Studying the intellectual origins of Islamic socialism in Indonesia, then, shows not only the roots of an important strand of Southeast Asian politics in the last century, but also the importance of alternative currents of thought (South Asian, outside the mainstream, Anglophone) in Southeast Asian Islam.